From the Act of Judging to the Sentence The Problem of Truth Bearers from Bolzano to Tarski - Rojszczak, Artur (Synthese Library, Studies in Epistemology, Logic, Methodology, and Philosophy of Science,, 2005)
This book offers a detailed study of the truth-bearers problem, that is, the question of which category of items the predicates 'true' and 'false' are predicated. The book has two dimensions: historical and systematic. Both focus around Tarski's semantic theory of truth. The author locates Tarski's ideas in a broad context of Austrian philosophy, in particular, Brentano's tradition. However, Bolzano and phenomenology (Husserl and Reinach) are also taken into account. The historical perspective is completed by showing how Tarski was rooted in Polish philosophical tradition originated with Twardowski and his version of Brentanism. The historical considerations are the basis for showing how the idea of truth-bearers as acts of judging was transformed into the theory of truth-bearers as sentences. In particular, the author analyses the way to nominalism in Polish philosophy, culminating in Lesniewski, Kotarbinski and Tarski. This book is indispensable for everybody interested in the evolution of Austrian philosophy from descriptive psychology to semantics. It is also a fundamental contribution toward a deeper understanding of the philosophical background of Tarski's theory of truth.